Revisión de la metodología empleada y resultados alcanzados en la investigación sobre actuación medioambiental de la empresa y rendimiento económico (1972-2009) - María Azucena Vicente Molina; Unai Tamayo Orbegozo; Julen Izaguirre Olaizola (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2012)
– The "environment" factor has become increasingly important in business management. The relationship between the environmental behavior of the company and its economic performance has been one of the recurring themes of research, especially in the last two decades. However, many gaps still exist in this field of study, such as the lack of a theoretical framework and a methodology that allow reliable research in order to empirically contrast and compare the results of the different studies. Thus, we found that the empirical evidence on this relationship sometimes presents contradictory results. Therefore, this work has two objectives. On the one hand, we review the existing literature in order to identify and systematize the type of studies, the analysis techniques, the key factors of such relationship, the shortcomings and limitations of these studies, etc. trying to throw some light on the sign of the target relation. On the other hand, we look for fostering critical reflection, and we make some suggestions for future research.
Keywords: Q56; Q59; M19; 330; quantitative methods; environmental performance; economic result; empirical evidence